2018
DOI: 10.1186/s13046-018-0872-6
|View full text |Cite|
|
Sign up to set email alerts
|

Liver cancer cell lines distinctly mimic the metabolic gene expression pattern of the corresponding human tumours

Abstract: BackgroundAlthough metabolism is profoundly altered in human liver cancer, the extent to which experimental models, e.g. cell lines, mimic those alterations is unresolved. Here, we aimed to determine the resemblance of hepatocellular carcinoma (HCC) cell lines to human liver tumours, specifically in the expression of deregulated metabolic targets in clinical tissue samples.MethodsWe compared the overall gene expression profile of poorly-differentiated (HLE, HLF, SNU-449) to well-differentiated (HUH7, HEPG2, HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 42 publications
10
80
2
Order By: Relevance
“…Our data indicate that metabolic alterations may contribute to the functional differences between these two tumor cell populations with different biological roles. Although the use of an in vitro model of PTC is a limit to our approach, the recent report that cancer cell lines distinctly mimic the metabolic gene expression pattern of the corresponding human tumors in liver [ 27 ] support the translation of our results, which for the first time indicate that cancer stem-like cells isolated from PTC-derived cell lines may be distinguished from the adherent cell population by a metabolomic approach, paving the road for in vivo studies.…”
Section: Introductionsupporting
confidence: 59%
“…Our data indicate that metabolic alterations may contribute to the functional differences between these two tumor cell populations with different biological roles. Although the use of an in vitro model of PTC is a limit to our approach, the recent report that cancer cell lines distinctly mimic the metabolic gene expression pattern of the corresponding human tumors in liver [ 27 ] support the translation of our results, which for the first time indicate that cancer stem-like cells isolated from PTC-derived cell lines may be distinguished from the adherent cell population by a metabolomic approach, paving the road for in vivo studies.…”
Section: Introductionsupporting
confidence: 59%
“…As a member of the acyl-CoA dehydrogenase family, ACADSB promotes the lipid metabolism via catalyzing the dehydrogenation of acyl-CoA derivatives (Arden et al, 1995). Earlier studies indicated that ACADSB might exert tumor suppressive function in poorly-differentiated hepatocellular carcinoma and kidney renal clear cell carcinoma (Nwosu et al, 2018;B. Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that ACADSB has the greatest activity towards the short-branched-chain acyl-CoA derivative, (S)-2-methylbutyryl-CoA, but also reacts with other 2-methyl branched-chain substrates and with short straight chain acyl-CoAs (Schwander et al, 2018). Nwosu et al (2018) reported that poorly-differentiated hepatocellular carcinoma cells showed low gene expression of ACADSB. B.…”
mentioning
confidence: 99%
“…HepG2 and Huh7 are well-differentiated hepatocarcinoma cell lines derived from a pediatric hepatoblastoma and an adult hepatocarcinoma biopsy, respectively [18][19][20][21].Cells were generously provided by Dr. Jordan Feld, Toronto Centre for Liver Disease, Toronto General Hospital and Dr. Michael Carpenter, Viral Diseases Division, National Microbiology Laboratory; and were maintained in Dulbecco's modified eagle media, supplemented with 10% fetal bovine serum, 2mM L-glutamine, and penicillin (100 IU/ml)/streptomycin (100μg/ml). All infection studies used Crimean Congo Hemorrhagic Fever virus (CCHFV) IbAr 10200 (accession numbers AY389508, AF467768, and CHU88410).…”
Section: Virus and Cellsmentioning
confidence: 99%